Challenges and solutions of oncological hyperthermia - Szasz, Andras, 1947- (Cambridge Scholars Publishing, 2020)
The next generation of oncological hyperthermia involves the medical innovation of selectively heating up the malignant cells of the body in a controlled way. The easily-distinguishable biophysical and physiological characteristics of cancer cells and their immediate environment are the focus of the targeted energy delivery of this treatment. This heterogenic heating concept breaks with the homogeneous nature of conventional hyperthermia, where an isothermally equal temperature is applied to the large surface area of a solid tumor.